Etnobotani Tumbuhan Pewarna Alami sebagai Hasil Hutan Bukan Kayu (Studi Kasus Desa Inbate, Kecamatan Bikominilulat, Kabupaten Timor Tengah Utara, Nusa Tenggara Timur) - Reynaldy Henuk; Astin E. Mau; Pamona Silvia Sinaga; Fadlan Pramatana (Wana Lestari, 2025)
Natural dye plants used by ikat weaving craftsmen in Inbate Village, Conservation efforts of natural dye plants in Inbate Village. This research was carried out in Inbate Village, Bikominilulat, North Central Timor Regency, East Nusa Tenggara which was carried out in June 2025. The results of the study show that the types of natural dye plants found in Inbate Village are pear cactus (Opuntia ficus- indica), Tarum (Indigofera tinctoria), Arbila (Phaseolus lunatus L), and Turmeric (Curcuma longa). The distribution of natural dye plants for ikat weaving in Inbate Village, Bikomi Nilulat District, North Central Timor Regency, found the most commonly used dye plant species in the ikat weaving artisan community in Inbate Village which are spread across several locations including yards, gardens and forests. Observations consisting of 27 points can be seen the distribution, namely the pear cactus (Opuntia ficus- indica) as many as 4 points, Tarum (Indigofera tinctoria L) as many as 10 points, Arbila (Phaseolus lunatus L) as many as 6 points, and Turmeric (Curcuma longa) as many as 7 points. The form of use of natural dye plants by the community in Inbate Village is as a basic material for natural dyes for ikat woven fabrics. In addition, conservation efforts carried out by the community to maintain the preservation of natural dye plants are by cultivating them in the yard of the house.